2001
DOI: 10.1097/00006534-200110000-00007
|View full text |Cite
|
Sign up to set email alerts
|

The Outcome of Failed Free Flaps in Head and Neck and Extremity Reconstruction: What Is Next in the Reconstructive Ladder?

Abstract: The indications for free flaps have been more or less clarified; however, the course of reconstruction after the failure of a free flap remains undetermined. Is it better to insist on one's initial choice, or should surgeons downgrade their reconstructive goals? To establish a preliminary guideline, this study was designed to retrospectively analyze the outcome of failed free-tissue transfers performed in the authors hospital. Over the past 8 years (1990 through 1997), 3361 head and neck and extremity reconstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
86
1
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(95 citation statements)
references
References 23 publications
7
86
1
1
Order By: Relevance
“…Technically difficult flaps were iliac crest or radial artery with bone. This is keeping with the literature where success goes up in the later part of series [31]. Greater anatomical flap dissection or surgical mentorship can help reduce this source of error.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Technically difficult flaps were iliac crest or radial artery with bone. This is keeping with the literature where success goes up in the later part of series [31]. Greater anatomical flap dissection or surgical mentorship can help reduce this source of error.…”
Section: Discussionsupporting
confidence: 78%
“…A culture of success is reflected in their failure rates which are historically low [8][9][10][11][12]17,28,31]. It's important to mention that when a variety of flaps or new flaps are used the success rate goes down with a thrombotic rate of 17.4%, even at centers of excellence [28].…”
Section: Discussionmentioning
confidence: 99%
“…27,7,10,12,13,16,18,22,23 Wei et al transferred 1235 flaps to the head and neck region over 8 years (1990-1997); among them were 42 failures (3.4%). 30 As in other series 10,15,21,29 the radial forearm flap was one of the most commonly used flap types for the treatment of intraoral defects. Macnamara et al 15 reported this type of flap to have the best functional and aesthetic outcome in their series of 60 patients receiving microvascular free flap transfer to the head and neck region.…”
Section: Discussionmentioning
confidence: 87%
“…A subsequent paper reported similar findings with a 7% re-exploration rate and an 80% salvage rate, of which 30% were partial flap salvage 2 . The best survival rates published are by WEI et al in which their overall failure rates are approximately 3%, with a 9% re-exploration rate 27 . A significant reduction in flap failure is achievable if flap ischaemia can be detected reliably and early.…”
Section: Discussionmentioning
confidence: 99%